Educational Psychology of mathematics - González Moreyra, Raúl (1998)
It was made a brief lo dale bibliographic revision to identify the state of psycho-pedagogic knowledge of mathematics leaching-learning. We found three defined thematics: the first about cognitive development of the mathematics concepts, the second about the process of calculating and solving of problems by the students and the third about the psycho-pedagogic strategies for school use. Respect the first theme we have reviewed two areas, early development (zero to 4-5 years) and operant development (post). We have considered the new findings in what is made on number in the pre-verbal child and maintained the piagetian ideas from the pre-conserving stages. About the second we have reviewed mistakes and precision on calculating, the abilities of accurate calculation and the function of memo,-y; also, aspects of problem solving as organization of knowledge of the cognitive process and the resolutory activity. In the third theme, which we divided in numerical psycho-didactics and conjunctivas, we have reviewed on one side the ideas of Thordnike, Gagné and Resnick and on the other from the Gestalt, Bruner y Dienes. The final balance is of a positive advance in knowledge and procedures about mathematics psycho-pedagogy.